THE IMPLEMENTATION OF PSAK 102 FOR MURABAHAH FINANCING; CASE STUDY IN SULSELBAR SYARIAH BANK MAKASSAR - Menne, Firman (Journal of Humanity, 2016)
This study aims to know the implementation of Murabahahh financing inSulselbar Syariah Bank Makassar and the conformity of its implementation to PSAKNo. 102. This study used descriptive comporative method to describe and indicatethe condition deeply the implementation of Murabahahh financing in PT BankSulselbar Syariah Makassar. The result of this research indicated that theimplementation of Murabahahh financing in PT Bank Sulselbar Syariah Makassarhas been suitable with PSAK 102 which sale and purchase agreement with the sellingprice of goods at cost plus an agreed profit which the seller must disclose theacquisition cost of the item to the buyer